Noticeability of Stencils: The Case of Kadıköy Caferağa - Citak, Kadir; Tuker, Cetin (ROUTLEDGE JOURNALS, TAYLOR & FRANCIS LTD, 2024)
This study investigates the noticeability of stencil prints containing various graphic elements in & Idot;stanbul, Turkey. A designated route was selected, and all stencil applications along this route were systematically documented. A total of 108 distinct stencil prints were identified and recorded, along with their corresponding locations. Eleven volunteers walked the route and completed an online questionnaire. The findings showed strong correlation between the frequency and recall of stencil prints only if they incorporate iconographic elements in addition to typographic elements. No correlation has been found between the average size of stencils and recall. Stencil prints with visual elements or a combination of visual and typographic elements were more likely to recalled than those with only typographic elements. These observations align with human cognitive architecture, suggesting that stencil prints connecting with existing information schemes are easily noticed and retained.
Keywords: COGNITIVE ARCHITECTURE; Communication